Development of CRISPR-Cas12a-based fluorescent assay for rapid detection of peanut mottle virus in quarantine: CRISPR-CAS12A-BASED FLUORESCENT ASSAY FOR DETECTION OF PEANUT MOTTLE VIRUS - B PARAMESWARI; A RAJASHREE; P ANBAZHAGAN; BHASKAR BAJARU; SATENDRA KUMAR MANGRAUTHIA; G GURU PIRASANNA PANDI; FAISAL YOUSUF; Y PRASANTHI; L SARAVANAN; V CELIA CHALAM (Journal of Oilseeds Research, 2025)
Peanut (Arachis hypogaea L.) is susceptible to infection by more than 31 viruses, with seed-borne viruses posing a major challenge to international trade and germplasm exchange. Among these, peanut mottle virus (PeMoV), a positive-sense single-stranded RNA virus of the genus Potyvirus, is one of the most economically significant pathogens, transmitted both through seeds and by aphids in a non-persistent manner. Therefore, an accurate and sensitive detection method for PeMoV is urgently required in quarantine samples. In this study, we developed a CRISPR/Cas12a-based visual detection system targeting the PeMoV coat protein gene combined with reverse transcription recombinase polymerase amplification (RT-PRA). The whole process can be completed within 60 to 90 min with high sensitivity. This system detected cDNAs diluted up to 10-8 when 100 ng of total RNA was used for reverse transcription. The Cas12a/crRNA complex specifically recognized and cleaved the target double-stranded DNA, subsequently degrading single-stranded DNA probes to generate fluorescent signals. The resulting green fluorescence under blue light (440-460 nm) was visible to the naked eye. The optimisation of gRNA: CAS12a concentration, ss-DNA reporter concentration, detection time and reaction temperature was performed to standardise the most efficient assay condition. This work represents the first report of an RPA-assisted CRISPR/Cas12a fluorescent assay for PeMoV detection, providing a rapid diagnostic tool to support germplasm health monitoring and quarantine practices.